"The Biological Yield and Harvest Index of Cereals as Agronomic and Plant Breeding Criteria" by C.M. Donald and J. Hamblin, Advances in Agronomy (1976) 28:361–405. Issue 3 (1st May 2019) - Sinclair, Thomas R.
Abstract : This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by C.M. Donald and J. Hamblin published in 1976 that provided original insights about the role of harvest index (defined by them as the ratio of economic yield to aboveground mass) in influencing crop yield. Donald and Hamblin reviewed experimental results showing that harvest index was relatively stable across variations in plant size, had high heritability, and was associated with high grain yield. Although their observations were confirmed in subsequent tests, inconsistent results in plant selection in breeding programs for high yield based on harvest index has discouraged the use of harvest index as a basis for selection. Nevertheless, high harvest index is now well ingrained as an essential plant characteristic for high crop yields.